Central retinal artery occlusion in patients with cerobro vascular accident in a teaching hospital in rural Telangana, India - N., Karthika; Madhavaram, Bharath; Kumar, Ashok (International Surgery Journal, 2019)
Background: Central retinal artery occlusion (CRAO) is a stroke of the eye caused by obstruction of the central retinal artery, usually by a thrombus or embolus that results in painless, disabling vision loss, hence it is an occular emergency. This study was done to know the visual outcomes in patients with CRAO. Methods: An observational study was conducted on the patients admitted with cerebrovascular accident at MediCiti Institute of Medical Sciences over a period of 2yrs i.e. from January 2015 to December 2016. The study included 75 patients with Cerebro-Vascular Accident (CVA) that met the inclusion criteria for diagnosis of CRAO. Results: A total of 75 cases with CVA admitted to the hospital were included in the study. The age group ranged from 50 to 80 years (median age 65 years). Among these, 64 cases were associated with hypertension and 46 cases with diabetes. Six patients (8%) had CRAO with sparing of cilio-retinal artery. Conclusions: CRAO has a diverse etiology. It can vary from hypertension to even snake bite. As it is an occular emergency, Identification of under lying cause is essential during follow-up for better intervention.